Facing Asia : a history of the Colombo Plan - Oakman, Daniel (ANU E Press, 2010)
"This book examines the public and private agendas behind Australia's foreign aid diplomacy and reveals the strategic, political and cultural aims that drove the Colombo Plan. It examines the legacy of WWII, how foreign aid was seen as crucial to achieving regional security, how the plan was sold to Australian and Asian audiences, and the changing nature of Australia's relationship with Britain and the United States. Above all this is the question of how Australia sought to project itself into the region, and how Asia was introduced into the Australian consciousness. In answering these questions, this book tells the story of how an insular society, deeply scarred by the turbulence of war, chose to face its regional future."--Publisher's description